Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1177/1368430206064636
|View full text |Cite
|
Sign up to set email alerts
|

Thanks for the Compliment? Emotional Reactions to Group-Level Versus Individual-Level Compliments and Insults

Abstract: The current research investigated participants' reactions to positive and negative comments directed toward them as individuals or as members of a social group. Using both perspective-taking (Studies 1 and 2) and actual interaction methodologies (Study 3), three studies found that participants generally responded negatively to negative comments regardless of the level of identity to which the comment was directed. Positive comments were generally viewed positively, except when the comment was directed at the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…R. Smith, , 1999 proposes that when social identities are salient, individuals who experience events that favor or harm their group will experience positive or negative affect on their group's behalf, rather than on behalf of their personal identities. Consistent with this, Garcia, Miller, Smith, and Mackie (2006) found that people who experienced verbal insults directed toward their group responded emotionally to the group-level event and consequently experienced group-based negative emotions and behavioral action tendencies, such as the desire to attack the source of the insult.…”
Section: Respect As An Intergroup Relational Concernsupporting
confidence: 52%
“…R. Smith, , 1999 proposes that when social identities are salient, individuals who experience events that favor or harm their group will experience positive or negative affect on their group's behalf, rather than on behalf of their personal identities. Consistent with this, Garcia, Miller, Smith, and Mackie (2006) found that people who experienced verbal insults directed toward their group responded emotionally to the group-level event and consequently experienced group-based negative emotions and behavioral action tendencies, such as the desire to attack the source of the insult.…”
Section: Respect As An Intergroup Relational Concernsupporting
confidence: 52%
“…Furthermore, genuine performance-based compliments that are qualiWed by the target's group membership are likely to yield negative reactions. Garcia, Miller, Smith, and Mackie (2006) found that participants reacted to group-qualiWed compliments (e.g., "You did really well for a woman!") with heightened anger and evaluated the person making the compliment as prejudiced.…”
Section: Discussionmentioning
confidence: 98%
“…The often compensatory relationship between outgroups’ inferred warmth and competence (Judd et al, 2005; Yzerbyt et al, 2008), and tight coupling of positive and negative stereotypes (Czopp & Monteith, 2006), mean that persistently emphasizing positive unidimensional outgroup stereotypes may hinder repair of closely linked (but unspoken) negative stereotypes on other dimensions. When White or male communicators respectively praise Blacks’ athletic ability or say “You did really well for a woman,” such allegedly positive “compliments” lead (Black or female) audiences to draw negative inferences about communicators’ impressions (Czopp, 2008; Garcia, Miller, Smith, & Mackie, 2006). Similarly, White communicators give more positive open-ended descriptions of Black than White targets, but audiences who know the targets’ race interpret these descriptions more negatively, forming worse impressions of Black than White targets (Collins, Biernat, & Eidelman, 2009).…”
Section: Discussionmentioning
confidence: 99%